High Stomatal Conductance in the Tomato Flacca Mutant Allows for Faster Photosynthetic Induction - Kaiser, Elias; Morales, Alejandro; Harbinson, Jeremy; Heuvelink, Ep; Marcelis, Leo F. M. (Frontiers in Plant Science, 2020)
Due to their slow movement and closure upon shade, partially closed stomata can be a substantial limitation to photosynthesis in variable light intensities. The abscisic acid deficient flacca mutant in tomato (Solanum lycopersicum) displays very high stomatal conductance (gs). We aimed to determine to what extent this substantially increased gs affects the rate of photosynthetic induction. Steady-state and dynamic photosynthesis characteristics were measured in flacca and wildtype leaves, by the use of simultaneous gas exchange and chlorophyll fluorometry. The steady-state response of photosynthesis to CO2, maximum quantum efficiency of photosystem II photochemistry (Fv/Fm), as well as mesophyll conductance to CO2 diffusion were not significantly different between genotypes, suggesting similar photosynthetic biochemistry, photoprotective capacity, and internal CO2 permeability. When leaves adapted to shade (50 µmol m-2 s-1) at 400 µbar CO2 partial pressure and high humidity (0.7 kPa7 mbar leaf-to-air vapour pressure deficit, VPD) were exposed to high irradiance (1500 µmol m-2 s-1), photosynthetic induction was faster in flacca compared to wildtype leaves, and this was attributable to high initial gs in flacca (~0.6 mol m-2 s-1): relative to the wildtype, in flacca, the times to reach 50 (t50) and 90% (t90) of full photosynthetic induction were reduced by 1091 and 12046% of wildtype values, respectively. Low humidity (1.5 kPa15 mbar VPD) reduced gs and slowed down photosynthetic induction in the wildtype, while no change was observed in flacca; under low humidity, t50 was reduced by 6063% and t90 was by 18036% of wildtype levels in in flacca relative to the wildtype. Photosynthetic induction in low CO2 partial pressure (200 µbar) increased gs in the wildtype (but not in flacca), and revealed no differences in the rate of photosynthetic induction between genotypes. Effects of higher gs in flacca were also visible in transients of photosystem II operating efficiency and non-photochemical quenching. Our results show that at ambient CO2 partial pressure, wildtype gs is a substantial limitation to the rate of photosynthetic induction, which flacca overcomes by keeping its stomata open at all times, and it does so at the cost of reduced water use efficiency.